2017
DOI: 10.18632/oncotarget.14435
|View full text |Cite
|
Sign up to set email alerts
|

High expression of miR-105-1 positively correlates with clinical prognosis of hepatocellular carcinoma by targeting oncogene NCOA1

Abstract: Increasing evidence supports that microRNA (miRNA) plays a significant functional role in cancer progression by directly regulating respective targets. In this study, the expression levels of miR-105-1 and its target gene were analyzed using genes microarray and hierarchical clustering analysis followed by validation with quantitative RT-PCR in hepatocellular carcinoma (HCC) and normal liver tissues. We examined the expression of nuclear receptor coactivator 1 (NCOA1), the potential target gene of miR-105-1, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The HCC mortality rate is the fastest growing among all types of cancer and it is the third most common cause of tumor-associated mortality (25)(26)(27). Although there have been improvements in surgery and other therapeutic methods, the 5-year survival rate has remained <15% for a number of years (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The HCC mortality rate is the fastest growing among all types of cancer and it is the third most common cause of tumor-associated mortality (25)(26)(27). Although there have been improvements in surgery and other therapeutic methods, the 5-year survival rate has remained <15% for a number of years (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that NCOA1 could also serve as a potential biomarker for ESCC prognosis. All these findings are consistent with the report that patients with NCOA1 overexpression along with low expression of miR‐105‐1 were closely associated with both poor overall survival and progression‐free survival in hepatocellular cancer …”
Section: Discussionmentioning
confidence: 99%
“…Although NCOA1 is the founding member of the p160 family, its functional roles in oncogenesis and progression are not as well‐established as that of SRC‐3, another member of the family with well‐defined oncogenic activity. It has been reported that NCOA1 can promote proliferation of both breast cancer and hepatocellular cancer cells . But results from mice with NCOA1 deletion suggest that NCOA1 is capable of promoting breast cancer metastasis without affecting primary tumor growth, and mechanistically proposed as through NCOA1 mediated crosstalk between tumor cells and their microenvironment .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations